Some vexations that challenge viral immunology - Rouse, Barry T. (F1000Res, 2016)
The field of viral immunology seeks to understand mechanisms of virus-host interaction with a view of applying this knowledge to the design of effective vaccines and immunomodulators that control viral infections. This brief review discusses several areas of the field that hold substantial promise for translation, but where further work is critically required to find solutions. We emphasize that our fundamental understanding of virus-host relationships is moving in leaps and bounds, but we lag behind in applying this knowledge to the successful control of many viral infections.